New benefit sharing rules for digital sequence information under the CBD and plant treaty. - Halewood, Michael (2024)
Part of the CGIAR Environment and Biodiversity Platform Webinar Series, in collaboration with the CGIAR Genebank Initiative. This webinar examined the current state of negotiations of both agreements and considered options for how they can be implemented in mutually supportive ways. The webinar brought together Co-chairs of the CBD and Plant Treaty negotiations along with representatives of key stakeholders in the agriculture sector including seed companies, farmer and civil society organizations and public researchers.